LEGAL ANALYSIS OF THE PRACTICE OF TRANSFER OF RIGHTS BY FINANCING INSTITUTIONS THROUGH AN ABSOLUTE POWER OF POWER: A REVIEW OF VIOLATIONS OF LAW AND ITS LEGAL IMPACT - Rohmawati, Indah; Khaerudin, Ariy; Yudanto, Dika (Awang Long Law Review, 2023)
This research aims to examine unlawful practices committed by financing institutions in the process of transferring rights by using absolute power of attorney and examine the legal consequences of using absolute power of attorney against the law. The research uses a statutory approach and applicable regulations along with legal principles used to examine the problem under study. The conclusion obtained is that in practice there are still many financing institutions in collaboration with authorized officials who still practice debt and credit mixed with buying and selling, therefore the use of absolute power of attorney in the transfer process is a legal act prohibited by laws and regulations which can be canceled and null and void and is a form of abuse of circumstances and vigilante efforts. The legal consequences of the practice of unilateral transfer of rights using an absolute power of attorney are a form of legal smuggling where when the conditions for the validity of the agreement are not met, which include subjective conditions in the form of an agreement containing elements of unlawful acts and objective conditions regarding legal causes because they violate the Civil Code and Presidential Instruction Number 14 of 1982 concerning the Prohibition of the Use of Absolute Power of Attorney as a Transfer of Land Rights which was later replaced and refined in Government Regulation No. 24 of 1997 concerning Land Registration.